3D morphological variability in foraminifera unravel environmental changes in the Baltic Sea entrance over the last 200 years - Choquel, Constance; Müter, Dirk; Ni, Sha; Pirzamanbein, Behnaz; Charrieau, Laurie M.; Hirose, Kotaro; Seto, Yusuke; Schmiedl, Gerhard; Filipsson, Helena L. (Frontiers in Earth Science, 2023)
Human activities in coastal areas have intensified over the last 200 years, impacting also high-latitude regions such as the Baltic Sea. Benthic foraminifera, protists often with calcite shells (tests), are typically well preserved in marine sediments and known to record past bottom-water conditions. Morphological analyses of marine shells acquired by microcomputed tomography (µCT) have made significant progress toward a better understanding of recent environmental changes. However, limited access to data processing and a lack of guidelines persist when using free software adaptable to different microfossil shapes. Here, we describe a post-data routine to analyze the entire test parameters: average thickness, calcite volume, calcite surface area, number of pores, pore density, and calcite surface area/volume ratio. We illustrate the efficiency of this post-data routine with a case study: 3D time series (i.e., 4D) of Elphidium clavatum specimens recording environmental conditions in the Baltic Sea entrance from the time period early industrial (the 1800s) to present-day (the 2010s). We demonstrate long-term morphological trends in the foraminiferal record, revealing that modern specimens have ~28 % thinner tests and ~91 % more pores than their historic counterparts. We find that inter-individual variability and flux variations (specimens cm-2 y-1) in E. clavatum are not always synchronous. While the flux remains unchanged, we document natural environmental fluctuations in the early industrial period and the consequences of anthropogenic climate change in the 21st century through large morphological variability. During the period from the 1940-2000s, the variations in foraminiferal flux are synchronous with inter-individual variability, revealing both the effects of the increase in human activities and major hydrographic changes. Finally, our interpretations based on E. clavatum morphological variations highlight environmental changes in the Baltic Sea area, similar to those documented by foraminiferal assemblages.